CLINICAL CONFERENCE AS A FORM OF INDEPENDENT WORK OF INTERNS - T.P. Skripnikova; M.V. Khrebor; Yu.I. Silenko (Український стоматологічний альманах)
The main objective of higher education is the formation of a creative personality specialist able to selfdevelopment, self-education, and innovation.